al-'Awāmil wa al-Asykāl fī Taţawwuri ad-Dalālah fī al-Lugah al-'Arabiyyah - Luthfi Muhyiddin; Ghazali Awaluddin (University of Darussalam Gontor, 2017)
Abstract Today, Arabic has become a universal language spoken by more than two billion Arab and non-Arab speakers throughout the countries in the world. Then, it is not the language of a particular people but all nations’ language. It is caused by the development that we feel from the inventions, creations, events, ideas and the new system of traditions and norms which makes people need to know the indications and the meaning that reflected from those developments. The development impacts every language of the world in use and meanings, even the Arabic language. The most developed elements of linguistic in human languages are the vocabularies, especially for the contemporary languages which always change its vocabularies every times and do not pass a century, but are affected by a fundamental change in the vocabularies and rules. The changes in Arabic are quite different which has a static foundation but changeable branches. This research aims to identify the heterogeneous factors of semantic changes in Arabic language, and the result is the existence of internal factors for the developments and changes in the semantic of Arabic language, there are: the acoustic factor, morphological factor, structure factor and other factors of linguistic. And the external factors are: social factor, historical factor, cultural factor and psychological factor. There are several forms of development of significance of semantic in the Arabic language such as, generalization if significance, the allocation of significance, the transmission of significance, the indication of significance and the decline of significance.Keywords: Development and change, semantic, significance, the factors, the forms. العَوَامِلُ وَالأَشْكَالُ فيِ تَطَوُّرِ الدِّلَالَةِ فيِ اللُّغَةِ العَرَبِيَّةِ(دراسة تحليلية وصفية)بقلم: لطفي محيي الدين و غـــزالي أوّل الدّينجامعة دار السلام كونتور الملخص أصبحت اللغة العربية اليومَ لغةً عالمية ينطق بها المتحدثون العرب وغيرهم من الأعاجم المنتشرين في جميع بلاد العالم، وهم أكثر من ملياري نسمة، فإنها بذلك، ليست لغة شعبٍ معينٍ من الشعوب، لكنها لغة جميع الأمم، وقد اختلف عالم الماضي عن العالم الذي نعِيش فيه الآن؛ بسبب التطوُّر الذي نَلمسُه ونَشعُرُ به بظهور المخترعات والإبداعات والأحداث والأفكار ونشأة النظم والتقاليد والأعراف الجديدة التي تجعل الناس محتاجين إلى دلالات جديدة تعبر عن هذه المتغيرات، فكل لغة من لغات العالم قابلة للتغيُّر والتطوُّر في معانيها أو دلالاتها، حتى اللغة العربية، وإن أكثر العناصر اللغوية قابليّة للتغيير في اللغات الإنسانية هي دلالات المفردات، لا سيما اللغات المعاصرة التي تتغير معاجمها بين الحين والحين، ولا يمر قرن إلا ويصيبها تغيير أساسي في مفرداتها وقواعدها، أما اللغة العربية فثابتة الأصول ومرنة الفروع. ويهدف هذا البحث على تعيين العوامل المتغايرات الدلالي فى اللغة العربية، وقد حصل على النتيجة هي وجود عوامل داخلية لتطوُّر الدلالة في اللغة العربية، ومنها: العامل الصوتي، والعامل الصرفي، والعامل النحوي، والعوامل اللغوية الأخرى، وعوامل خارجية، هي: العامل الاجتماعي، العامل التاريخي، العامل الثقافي، العامل النفسي. أما أشكال تطوُّر الدلالة في اللغة العربية، فهي: تعميم الدلالة، وتخصيص الدلالة، وانتقال الدلالة، ورقي الدلالة، وانحطاط الدلالة.الكَلِمَاتُ الرَّئِيسَةُ: تَطَوُّر، الدِّلَالَةُ، العَوَامِلُ، وَالأَشْكَالُ